A handbook of Romanticism studies - Faflak, Joel.; Wright, Julia M. (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, 2012)
The Handbook to Romanticism Studies is an accessible and indispensible resource providing students and scholars with a rich array of historical and up-to-date critical and theoretical contexts for the study of Romanticism. Focuses on British Romanticism while also addressing continental and transatlantic Romanticism and earlier periods; Utilizes keywords such as imagination, sublime, poetics, philosophy, race, historiography, and visual culture as points of access to the study of Romanticism and the theoretical concerns and the culture of the period; Explores topics central to Romanticism studies and the critical trends of the last thirty years.
Front Matter -- Introduction / Joel Faflak, Julia M Wright -- Aesthetics and Media. Imagination / Richard C Sha -- Sensibility / Julie Ellison -- Sublime / Anne Janowitz -- Periodicals / Kristin Flieger Samuelian, Mark Schoenfield -- Visual Culture / Sophie Thomas -- Theories of Literature. Author / Elizabeth A Fay -- Reader / Stephen C Behrendt -- Poetics / Jacqueline Labbe -- Narrative / Jillian Heydt-Stevenson -- Drama / David Worrall -- Gothic / Jerrold E Hogle -- Satire / Steven E Jones -- Ideologies and Institutions. Historiography / Ted Underwood -- Ideology / Orrin N C Wang -- Nation and Empire / Julia M Wright -- Class / Michael Scrivener -- Race / Peter J Kitson -- Gender and Sexuality / Kari Lokke -- Disciplinary Intersections. Philosophy / Marc Redfield -- Religion / Michael Tomko -- Science / Theresa M Kelley -- Medicine / James Robert Allard -- Psychology / Joel Faflak -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: 1700-1899; English literature -- 19th century -- History and criticism -- Handbooks, manuals, etc; English literature -- 18th century -- History and criticism -- Handbooks, manuals, etc; Romanticism -- Great Britain; Literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature; Romanticism; Englisch; Literatur; Romantik; Literatur; Romantik; Great Britain; Englisch; Electronic books; Criticism, interpretation, etc; Handbooks and manuals